Performance Analysis of Resilient Modulus and Fatigue Resistance of AC-BC Mixture with Full Extracted Asbuton and Reclaimed Asphalt Pavement (RAP) : Performance Analysis of Resilient Modulus and Fatigue Resistance of AC-BC Mixture with Full Extracted Asbuton and Reclaimed Asphalt Pavement (RAP) - Thopan Andhika Putra; Bambang Sugeng Subagio; Eri Susanto Hariyadi (Institut Teknologi Bandung, 2021)
Abstract One way to be developed to overcome challenges in providing flexible pavement materials is to apply the green roads principle by reusing some or all of the old road pavement material or Reclaimed Asphalt Pavement (RAP) as a material for new road pavement, which if reused will affect the performance of the mixture, such as decreasing the level of durability and premature pavement damage, so an effort must be made to improve the performance of the recycled material, namely by adding full extracted Asbuton and rejuvenating materials. The RAP material was obtained from scratching the asphalt of the Jagorawi Toll Road. The mixture used was asphalt concrete-binder course (AC-BC) layer using 30%, 40%, and 50% RAP material, using full extracted Asbuton at 6%, and Nichireki rejuvenating material. Then, on mixtures with RAP material, Marshall Test, Resilient Modulus test with UMATTA, and resistance to fatigue with four points loading test with strain control were conducted. The use of RAP material with modified asphalt in the form of an addition of full extracted Asbuton into the Pen 60/70 Asphalt can increase the asphalt stiffness. Marshall test results showed that a mixture with 6% full extracted asbuton content and 0% RAP material content (A6RAP0) gave the highest stability value. The results of the Resilient Modulus test showed that the mixture with 6% full extracted asbuton content and 50% RAP material content (A6RAP50) gave a high Resilient Modulus value at a test temperature of 45oC. The results of the fatigue resistance test showed that the mixture with 6% full extracted asbuton content and 50% RAP material content (A6RAP50) at a strain level of 300 µε gave the longest fatigue life. Keywords: Reclaimed asphalt pavement (RAP), full extracted asbuton, asphalt concrete -binder course, modified asphalt, resilient modulus, fatigue life. Abstrak Salah satu cara dikembangkan untuk mengatasi tantangan dalam penyediaan material perkerasan lentur adalah menerapkan prinsip greenroads dengan memanfaatkan kembali sebagian atau keseluruhan material perkerasan jalan lama atau Reclaimed Asphalt Pavement (RAP) sebagai material untuk perkerasan jalan yang baru, dimana jika digunakan kembali akan mempengaruhi kinerja dari campuran seperti penurunan tingkat durabilitas dan kerusakan dini perkerasan, sehingga harus dilakukan suatu upaya untuk memperbaiki kinerja dari material daur ulang tersebut, yaitu dengan penambahan Asbuton murni dan bahan peremaja. Material RAP didapatkan dari hasil garukan aspal Jalan Tol Jagorawi. Campuran yang dipakai adalah Laston Lapis AC-BC menggunakan kadar material RAP sebanyak 30%, 40%, dan 50%, dengan penggunaan Asbuton murni sebesar 6%, serta bahan peremaja Nichireki, dan kemudian selanjutnya pada campuran dengan penggunaan material RAP dilakukan pengujian Marshall, Modulus Resilien dengan alat UMATTA dan ketahanan terhadap kelelahan (fatigue) metode four points loading test dengan kontrol regangan. Penggunaan material RAP dengan aspal modifkasi berupa penambahan Asbuton murni kedalam Aspal Shell Pen 60/70 dapat meningkatkan kekakuan aspal. Hasil pengujian Marshall menunjukkan campuran dengan kadar Asbuton murni 6% dan kadar material RAP 0% (A6RAP0) memberikan nilai stabilitas tertinggi. Hasil pengujian Modulus Resilien menunjukkan campuran campuran dengan kadar Asbuton murni 6% dan kadar material RAP 50% (A6RAP50) memberikan nilai Modulus Resilien yang tinggi pada temperatur pengujian 45oC. Hasil pengujian ketahanan terhadap kelelahan menunjukkan campuran dengan kadar Asbuton murni 6% dan kadar material RAP 50% (A6RAP50) pada regangan 300 µε memberikan umur kelelahan yang paling panjang. Kata-kata kunci: Reclaimed asphalt pavement (RAP), Asbuton murni, laston lapis antara, aspal modifikasi, modulus resilien, umur kelelahan.